Analysis of Micro Structure, Porosity Disability and Wear Resistance with Volume Variation from Riser On the Engine Cover of Electric Motors - Rizal Rahma Sandi; Dieta Wahyu Asry Ningtias; Heri Yudiono (Journal of Electronics Technology Exploration, 2023)
This research to analyze the microstructure, porosity defects, and wear resistance of aluminum casting in the presence of variations in the volume of risers. The method used is the pre-experimental method of the One-Shot Case Study type, because in this study a treatment will be carried out and the results will be observed. The treatment that will be carried out is the addition of variations not using risers, variations of riser cylinders with a volume of 2826mm3, variations of riser cylinders with a volume of 4710mm3, variations of riser cylinders with a volume of 6594mm3. Microstructure testing used the Meji Techno IM 7200 test tool. Wear testing used the Ogoshi High Speed Universal Wear Testing Machine (Type OAT-U). The data analysis used is descriptive analysis to provide an overview of the research subject based on data from the variables obtained from the group of subjects studied. The best microstructure is shown by the cast specimens with the riser volume variation of 6594mm3 as evidenced by the formation of a more dense and even structural phase. The best porosity results were shown by the specimens that were cast with a volume variation of the riser 6594mm3 of 37.97%. The best wear resistance results in variations of the volume riser 6594mm3 with wear values of 0.51x10-7mm2/kg.